PENGARUH KOMPETENSI DAN WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA GURU YANG DIMEDIASI OLEH KOMITMEN ORGANISASI PADA SMA NEGERI 1 HUTABAYURAJA - Alfani, Tessa; Pardede, Henry Dunan; Calen, Calen; Nathania, Beatrice; Yunus, Muhammad (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
Human resources as teaching staff in the teaching process are teacher. One of them is that the number of teachers has increased from year to year. Many of those who have chosen this job and are married generally face work-life balance in managing work and personal life. In addition, greater job demands make some teachers have a negative attitude towards work which arises from dissatisfaction with work. This research aims to see the effect of work-life balance on job satisfaction among teachers at SMA Negeri 1 Hutabayuraja. This research uses a quantitative method which functions as a basis for formulating problems or questions, because this research aims to explain and test a predetermined path analysis with a total of 30 respondents. The results of research using the SPSS program show that Competency has a positive and significant effect on job satisfaction, Work-life Balance has a positive effect on job satisfaction, Organizational Commitment has a positive and significant effect on job satisfaction, Organizational Commitment mediates between Competency and Work-life Balance on Job Satisfaction at SMA Negeri 1 Hutabayuraja. Data processing uses the SPSS application.